WTO after Seattle - Schott, Jeffrey J. ed. (Institute for International Economics WashingtonUS, 2000)
Analyzes the problems and challenges facing the trading system in the aftermath of the Seattle ministerial. Examines why it is in the interests of both developed and developing countries to reengage in new trade talks, and how such talks could promote world trade and economic development, reform WTO operations, and strengthen public support for the trading system. Addresses the WTO's existing mandate to negotiate on agriculture and services, as well as how to handle issues such as investment, competition policy, e-commerce, and trade-related environmental and labour issues.